Comparative effectiveness of a low-calorie diet combined with acupuncture, cognitive behavioral therapy, meal replacements, or exercise for obesity over different intervention periods: A systematic review and network meta-analysis - Kim, Seo-Young; Shin, In-Soo; Park, Young-Jae (Frontiers in Endocrinology, 2022)
Objective The aim of this study was to evaluate the comparative effectiveness of a low-calorie diet (LCD) combined with acupuncture, cognitive behavioral therapy (CBT), meal replacements (MR), and exercise on weight loss. Methods The electronic databases MEDLINE, EMBASE, CENTRAL, CNKI, RISS, and KISS were searched systematically. Randomized controlled trials (RCTs) that directly compared the effect of a low-calorie diet (LCD)-combined acupuncture, CBT, and exercise and an MR-based diet on weight loss with LCD-alone for adults with simple obesity (body mass index [BMI] > 25) published before August 2021 were included in the study. Two investigators extracted and coded the data using a template. Any disagreements between investigators were resolved through discussion. Changes in BMI or weight were transformed to Hedges’ g values with a 95% CI, and network meta-analyses using a Bayesian random-effects model were conducted. Results A total of thirty-two trials involving 3,364 patients were finally included in the study. The effect sizes of four interventions were medium, in the order of acupuncture (Hedges’ g = 0.48, 95% CI = 0.25 - 0.71), CBT (Hedges’ g = 0.42, 95% CI = 0.20 - 0.63), MR (Hedges’ g = 0.32, 95% CI = 0.19 - 0.45), and exercise (Hedges’ g = 0.27, 95% CI = 0.06 - 0.46). In terms of intervention period, acupuncture was effective in the short period (≤ 12 weeks, Hedges’ g = 0.39, 95% CI = 0.12 - 0.67) and the long period (>12 weeks, Hedges’ g = 0.89, 95% CI = 0.37 - 1.40), whereas CBT (Hedges’ g = 0.51, 95% CI = 0.26 - 0.76) and exercise (Hedges’ g = 0.37, 95% CI = 0.12 - 0.59) were effective only in the long period. MR was effective only in the short period (Hedges’ g = 0.35, 95% CI = 0.18 - 0.53). Conclusions This study suggests that acupuncture, CBT, MR, and exercise for simple obesity show a medium effect size, and their effectiveness differs according to the intervention period.